Gambaran Stres dan Citra Tubuh pada Penduduk Usia 18-30 Tahun pada Masa Pandemi Covid 19 - Ade Individ Makal; Marsella Dervina Amisi; Yulianty Sanggelorang (Universitas Sam Ratulangi, 2021)
Background: Young adult is a population of productive age who has a very important role. During the Covid-19 pandemic, the government imposed restrictions on community activities that caused stress on young adults. This policy also leads to lack of physical exercise and irregular eating patterns, This causes weight gain and affects body image. The purpose of this study was to description the stress and body image in young adults in Bahu Village, Malalayang District, Manado City, during the Covid19 pandemic. Methods: This study is a descriptive study, carried out in February - July 2021 in Bahu Village, Malalayang District, Manado City. The sampling method used simple random sampling by taking a sample of 78 respondents. This study uses a questionnaire instrument where the assessment indicator uses the Perceived Stress Scale-10 (PSS-10) to measure stress, while to measure body image using the Body Shape Questionnaire-16 (BSQ-16). The data analysis method used is univariate data analysis. Results: The results showed that the stress variable showed that the young adults in Bahu Village, Malalayang District, Manado City who experienced stress as many as 52 people (66.7%), while 26 people (33.3%) did not experience stress. The results of the study of the body image variables showed that 45 people (57.7%) had a negative body image and 33 people (2.3%) had a positive body image. Conclusion: That can be conclude that the most of the young adults in Bahu Village, Malalayang District, Manado City during the Covid-19 pandemic experienced stress and had a negative body image.Based on this, respondents need to control the stress conditions experienced and for respondentswith negative body image it is necessary to respect themselves more and be grateful for theappearance they already have.